URGENSI DAN KONTRIBUSI OBSERVATORIUM AL-AFAQ UIN MATARAM DALAM PENGEMBANGAN FIKIH SAINS ASTRONOMI DI NUSA TENGGARA BARAT - Arino Bemi Sado; Muhammad Harfin Zuhdi (Universitas Islam Negeri Mataram, 2020)
The observatory is a building containing permanently-installed optical equipment used to view and examine celestial bodies or events related to space. The position of Al-Afaq observatory is very important, especially for the Islamic (Falak) science faculty of the Sharia UIN Mataram to improve the skills of students and the community in West Nusa Tenggara, especially for school students from the kindergarten to higher education that has only seen the celestial bodies through photographs, but with the presence of this observatory, they can see the celestial objects in real. The availability of this observatory is a major requirement for the advancement of Science, especially astronomical fiqh that seeks to understand the verses of kauniyah in the Qur’an. So that we can understand the Divine secrets that exist in the Word of God